Unveiling the strengthening effect of Nb in Ti3SiC2/Ti25Zr25Ni25Cu25 + Nb/GH3536 brazed joint - Xin Nai; Peng Wang; Shuai Zhao; Haiyan Chen; Pengcheng Wang; Achilles Vairis; Wenya Li (Journal of Materials Research and Technology)
In order to achieve the ceramic/metal brazed joint with excellent mechanical properties, many kinds of high-entropy alloy (HEA) filler have been developed to acquire the joint. However, in some HEAs with high content of active element, such as Ti25Zr25Ni25Cu25 amorphous HEA, the metallurgical reaction between active element and base materials resulted in the formation of continuous intermetallics (IMCs) layer in the brazing seam inevitably, embrittling the brazed joint. In this study, Nb element was added into Ti25Zr25Ni25Cu25 amorphous HEA filler to improve the microstructure of Ti3SiC2/GH3536 brazed joint, promoting the application of Ti3SiC2 and GH3536 in the aerospace industry. After detailed characterizations, the strengthening effect of Nb in the brazed joint was unveiled. The formation of Nb-base solid solution in the brazing seam was achieved owing to the addition of Nb, which effectively inhibited the generation of large brittle IMCs bulk. Moreover, the Nb-strengthened ZrSi2 and Ni2Ti phases were generated in the reaction zone, which was also favor in promoting the mechanical properties of brazed joints. When Ti25Zr25Ni25Cu25 amorphous HEA filler with 20 vol% Nb was applied to braze Ti3SiC2 to GH3536, a maximum value of 85.36 ± 2.39 MPa for shear strength was achieved. This study illustrates the optimization mechanism of Nb in Ti25Zr25Ni25Cu25 +Nb composite filler and promotes the further application of Ti25Zr25Ni25Cu25 in brazing system.